Bibliometric Analysis: The Potential of Beetroot (Beta vulgaris) for Diabetes Patients - Friska Feria Donza; Elsa Yuniarti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
This research aims to conduct a comprehensive bibliometric analysis of scientific publications on the potential of beetroot (Beta vulgaris) for diabetes patients. A quantitative method was employed by systematically collecting data from the Scopus database covering the period 2014-2023, using the specific keywords